PERAN BARISAN PEMUDA INDONESIA DALAM KEMERDEKAAN INDONESIA DI KOTA MEDAN TAHUN 1945 - Juraidah Hasibuan; Echa Wulandari; Yoseph Vincent Panggabean; Syahru Muharami Simanjuntak (Puteri Hijau : Jurnal Pendidikan Sejarah, 2023)
This research purposes to find out the context of the formation of Barisan Pemuda Indonesia (BPI) in the city of Medan and the role of the BPI  in achieving and maintaining independence. The method used in this study was library research by collecting books and documents related to the research topic as initial data, which were then analyzed. The establishment of Barisan Pemuda Indonesia (BPI) in the city of Medan did not take long because of the city's existence as a city of movement. Several important figures from this organization have contributed to the struggle since the Dutch government, including young pioneers who joined the Gyugun organization during Japanese military rule. Barisan Pemuda Indonesia (BPI) in Medan was determined to realize and defend independence and played a very important role in the Battle of Medan Area on October 13, 1945. These efforts included quoting news from foreign radio transmitters, publishing them in stenciled leaflets, and disseminating them to the public. Since then the city of Medan and its surroundings has been filled with news of the struggle for independence in Java and other struggle activities which made the people anxious to hear the news of the struggle for independence which stimulated the souls of the masses of the people to launch a revolution to realize the Proclamation of Independence on August 17, 1945 and are willing to die to defend it.